Pro-sociality and strategic reasoning in economic decisions - Arruñada, Benito; Casari, Marco; Pancotto, Francesca (Frontiers in Behavioral Neuroscience, 2015)
We study the relationship between pro-social preferences and strategic reasoning. These aspects are typically studied separately but little is known about their joint distribution. In an experiment, for each participant we elicit individual concerns toward pro-sociality - inequality aversion and efficiency - as well as the number of steps of reasoning through a guessing game. We report that self-regarding and pro-social participants exhibit similar levels of strategic reasoning, which supports the view that pro-sociality and strategic reasoning can be studied independently.